Investigating the visual privacy of house layouts in NEGERI Sembilan Traditional Malay Houses/ Noor Hayati Ismail, Azhani Abd. Manaf and Syazwani Zamri - Ismail, Noor Hayati; Abd. Manaf, Azhani; Zamri, Syazwani (Universiti Teknologi MARA, Perak, 2023)
A house is one of the necessities in the life of every human being. It is more than simply a shelter or structure but also significant in providing privacy to its occupants. This study aims to investigate the visual privacy regulated in different types of Negeri Sembilan Traditional Malay House (TMH). Different types of house layouts based on the number of pillars were selected in order to investigate the visual privacy. The research methodology utilizes case studies which include observations and interviews. Both case study portrays that visual privacy is regulated in Negeri Sembilan TMH despite the size of the house. The houses provide the need for visual privacy while maintaining and preserving community intimacy, social interaction and hospitality. This study is expected to be an eye-opener on the visual privacy regulated by occupants in Negeri Sembilan TMH.